2020
DOI: 10.1093/hmg/ddaa123
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal increases in somatic mosaicism of the expanded CTG repeat in myotonic dystrophy type 1 are associated with variation in age-at-onset

Abstract: In myotonic dystrophy type 1 (DM1), somatic mosaicism of the (CTG)n repeat expansion is age-dependent, tissue-specific, and expansion-biased. These features contribute toward variation in disease severity and confound genotype to phenotype analyses. To investigate how the (CTG)n repeat expansion changes over time, we collected three longitudinal blood DNA samples separated by 8 to 15 years and used small pool and single molecule PCR in 43 DM1 patients. We used the lower boundary of the allele length distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…The methylation levels of both upstream and downstream CpG sites were relatively stable over time in the blood samples of the patients. This differs from a recent study, where a tendency of decreasing methylation levels over time was observed in DM1 patients [32]. However, the sample size of this study was small (n = 3) and only included patients with methylation levels over 10% either upstream or downstream.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The methylation levels of both upstream and downstream CpG sites were relatively stable over time in the blood samples of the patients. This differs from a recent study, where a tendency of decreasing methylation levels over time was observed in DM1 patients [32]. However, the sample size of this study was small (n = 3) and only included patients with methylation levels over 10% either upstream or downstream.…”
Section: Discussionmentioning
confidence: 69%
“…Our results show significantly higher methylation levels at the downstream CpG sites in patients compared to controls, despite a few patients exhibiting methylation levels comparable to the mean value of the methylation levels of the controls ( Figure 2 B). In previous studies of non-congenital DM1-patients, both constitutive hypomethylation [ 21 , 23 , 31 ] and hypermethylation in a proportion of the patients, primarily those with longer (>600) repeats [ 4 , 19 , 32 ], have been reported. However, elevated methylation levels downstream of the repeat have been reported in patients with shorter (<500) repeats in a recent study [ 20 ], and we report in the present study that the methylation levels of downstream CpG sites are elevated in most DM1 patients compared to in controls, regardless of repeat length and parental transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Although the MMR system drives CAG repeat expansion, the overall increase in CAG repeat number may be a net consequence of individual expansion and contraction events. This type of expansion "biased" instability has been documented in the blood of DM1 patients [178,179]. Bidirectional CAG somatic and intergenerational instability has also been observed in both DM1 and HD mouse models, with longer inherited CAG or CTG repeat tracts subject to higher rates of contraction versus expansion [170,171,175,180].…”
Section: Genetic Evidence For the Role Of Mmr In Hdmentioning
confidence: 92%
“…Alternatively, expansion can occur by inclusion of an extrahelical extrusion into the primary structure of the DNA. Overall expansion may be a net result of individual expansion and contraction events, as has been suggested to occur in both HD and DM1 [178,179]. In fact, there is evidence that recruitment of DNA polymerase ␤ (Pol␤) by MutS␤ to CAG or CTG extrusions triggers error-prone DNA resynthesis in vitro, resulting in expansions [201].…”
Section: Mechanisms Of Mmr-mediated Cag Repeat Expansionmentioning
confidence: 99%
“…Recently, an important aspect of the pathogenesis of DM1 regarding to somatic expansion has attracted increasing attention. It has been demonstrated that the length of modal allele in blood DNA samples of DM1 patients increased over time, driven primarily by the inherited progenitor allele length (ePAL), age-at-sampling, and age-at-onset ( Morales et al, 2020 ). Since the DNA mismatch repair proteins MSH2, MSH3, and MSH6, are considered critical players in CTG repeat expansion, and their decreased expressions inhibit the expansion ( Dragileva et al, 2009 ; Tomé et al, 2009 ), they provide a new insight into the mechanism of CTG repeat instability in DM1.…”
Section: Molecular Mechanismsmentioning
confidence: 99%